CLIMATE CHANGE AS A TRIGGER OF GLOBAL SECURITY ISSUES - Sumadinata, Widya Setiabudi (Sean Institute, 2023)
This study aims to explain how climate change can affect various aspects of global security issues such as increasing global temperatures, extreme weather, and decreasing availability of clean water, which can trigger global security issues such as conflict and mass migration. In addition, this study also aims to identify climate change from the perspective of human security. This research uses a qualitative approach with descriptive methods. The research results show that climate change can become a global threat where shortages of water, food, and natural disasters will force the population of a nation to make every effort to fulfill their needs, including migrating. This of course can lead to conflicts such as the conflicts that occurred in Africa and South Asia. From a human security perspective, the issue of climate change also makes people feel insecure, especially in the seven areas of security, namely economic security, food security, health security, environmental security, individual security, community security, and political security. This of course will also have an impact on global security. Lastly, decisive action is needed to deal with climate change, considering the magnitude of the risks at stake, including forcing countries to obey and comply through the UN security council.